Literatur Review : Motivasi Belajar di Era Serba Digital: Array - Citra Bella Prawita; Neviyarni (eductum: Jurnal Literasi Pendidikan, 2022)
This literature review explains how the motivation to learn in today's all-digital era. This research was conducted by searching international and national literature related to the topics discussed using the Crossref, Google Schooler, and Microsoft Academic databases with the keywords learning motivation and technological development and the influence of gadgets. based on the results of the investigation, that in an all-digital era it can affect learning motivation, both positive and negative, this is limited by parental supervision.